2011
DOI: 10.1352/1944-7558-116.6.401
|View full text |Cite
|
Sign up to set email alerts
|

Overweight and Obesity Among Adults With Intellectual Disabilities Who Use Intellectual Disability/Developmental Disability Services in 20 U.S. States

Abstract: The authors compare the prevalence of obesity for National Core Indicators (NCI) survey participants with intellectual disability and the general U.S. adult population. In general, adults with intellectual disability did not differ from the general population in prevalence of obesity. For obesity and overweight combined, prevalence was lower for males with intellectual disability than for the general population but similar for women. There was higher prevalence of obesity among women with intellectual disabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
95
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(110 citation statements)
references
References 28 publications
15
95
0
Order By: Relevance
“…Our findings show that women were more likely to be overweight, obese, and have abdominal obesity than men. These sex-based differences are similar to those documented in smaller scale studies conducted in the USA, UK, and South Africa, 1,2,19,22,23 and two larger studies from the USA 28,32 and an earlier international study with Special Olympics participants. 10 The logistic regression analyses also revealed that age was a significant predictor of overweight, obesity, and abdominal obesity.…”
Section: Resultssupporting
confidence: 83%
“…Our findings show that women were more likely to be overweight, obese, and have abdominal obesity than men. These sex-based differences are similar to those documented in smaller scale studies conducted in the USA, UK, and South Africa, 1,2,19,22,23 and two larger studies from the USA 28,32 and an earlier international study with Special Olympics participants. 10 The logistic regression analyses also revealed that age was a significant predictor of overweight, obesity, and abdominal obesity.…”
Section: Resultssupporting
confidence: 83%
“…Interestingly, Hsieh et al (2014) reported the rates of morbid obesity among a younger population of adults with intellectual disability (i.e., 18 to 39 years) to be almost twice that reported in the general population and comparable with the 40-to 59-year-old age group. While others (Stancliffe et al, 2011) showed that participants were reportedly less likely to be overweight if they were older, Patka and Murry (2016) indicated that the prevalence of obesity decreased with adulthood only for men while the BMI continued to increase with age for women.…”
Section: Agementioning
confidence: 99%
“…While some researchers have found higher prevalence of both being overweight and obese among individuals with intellectual disability than the general healthy population (Emerson et al, 2016;Haider et al, 2013;Melville et al, 2008Melville et al, , 2007de Winter et al, 2012), others report only the prevalence of obesity and morbid obesity being higher than the general population (Hsieh et al, 2014). Moreover, one report (Stancliffe et al, 2011) highlighted the same prevalence of obesity as the general population, and another found people with severe or profound intellectual disability being significantly more likely than their peers to be underweight (Hsieh et al, 2014).…”
Section: Prevalence Of Being Overweight and Obesementioning
confidence: 99%
See 1 more Smart Citation
“…Primarily, the included studies were cross-sectional observational (n = 31 81,82,98,[100][101][102]104,106,[109][110][111]114,116,119,121,124,[126][127][128][129][130][131][132][133][134][135]137,139,142,143,145 ). The remaining studies involved retrospective database or medical records data (n = 22 [83][84][85][86][87][88][89]94,95,99,107,113,115,117,118,120,122,123,136,…”
Section: Study Characteristicsmentioning
confidence: 99%